A method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer

By adopting a new polymer preparation method in lithium-ion battery electrolyte, composite or gel polymer electrolyte is formed, the balance problem of existing electrolytes between mechanical properties and ionic conductivity is solved, and efficient lithium ion transmission is achieved And battery performance improvement.

CN119133615BActive Publication Date: 2025-02-18HUNAN DAJING NEW MATERIAL CO LTD
View PDF 6 Cites 0 Cited by

Patent Information

Application Number
CN202411596025.2
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2024-11-11
Publication Date
2025-02-18
Estimated Expiration
2044-11-11

AI Technical Summary

Technical Problem

The existing lithium-ion battery electrolytes cannot improve ionic conductivity while ensuring good mechanical properties, and in extreme environments, the problems of thermal runaway and low-temperature discharge performance are prone to problems.

Method used

Using a high-efficiency lithium-ion battery electrolyte preparation method based on new polymers, the lithium salt, organic plasticizer, polymer matrix and functional additives are uniformly dispersed in the solvent, and the composite polymer electrolyte or gel is formed through polymerization reaction. Polymer electrolytes improve the ionic conductivity and self-healing ability of the electrolyte.

Benefits of technology

It realizes rapid transmission of lithium ions in low-temperature environments, reduces migration resistance during ion transmission, improves the cycling efficiency and overall performance of the battery, extends the service life of the electrolyte, and significantly improves the low-temperature discharge performance and heat of the battery stability.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
Patent Text Reader

Abstract

The present invention discloses a method for preparing an efficient lithium-ion battery electrolyte based on a novel polymer, and relates to the technical field of battery electrolytes. The polymer electrolyte of the present application can achieve high ion conductivity through reasonable molecular design and polymerization reaction, ensure rapid transmission of lithium ions in the battery, reduce the migration resistance of ions during transmission, effectively improve the ionic conductivity of the electrolyte, and ensure that lithium ions can still migrate quickly and smoothly between positive and negative electrodes in a low-temperature environment, thereby avoiding the problem of discharge capacity attenuation caused by decreased conductivity, so that the battery can still maintain a high working efficiency under extremely cold conditions, and by adding a variety of different functional additives, reduce the diffusion resistance of lithium ions in the electrolyte, reduce its non-selective reaction on the electrode surface, thereby improving the cycle efficiency and overall performance of the battery.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the technical field of battery electrolytes, and in particular to a method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer. Background Art

[0002] Compared with traditional liquid electrolytes, polymer electrolytes have excellent thermal stability and chemical stability, which can effectively reduce the risk of thermal runaway of batteries under high temperature or short-circuit conditions and reduce safety issues caused by electrolyte leakage. However, existing lithium-ion battery electrolytes cannot improve ionic conductivity while ensuring good mechanical properties, and have certain defects.

[0003] The defects of the existing lithium ion battery electrolyte preparation method are:

[0004] 1. In the application document CN104752770A, the main consideration is how to improve the battery capacity and cycle performance of lithium-ion batteries under high voltage, but it does not take into account that the existing lithium-ion battery electrolyte cannot improve the ion conductivity while ensuring good mechanical properties;

[0005] 2. In the application document CN109546205A, the main consideration is how to enhance the compatibility of polymers, and it does not take into account that the existing lithium-ion battery electrolyte does not have the self-repair function;

[0006] 3. In the patent document CN108134128A, the main consideration is how to reduce the capacity attenuation of the battery cell at the side during the cycle charge and discharge process, but it does not take into account the problem that the existing lithium-ion battery electrolyte is prone to thermal runaway when used in extreme environments, and the battery has poor thermal stability;

[0007] 4. In patent document CN111916835A, the main consideration is how to avoid the problem of cross-linking and increased viscosity caused by adding two polymer monomers to the electrolyte, but it does not take into account that the low-temperature discharge performance and cycle stability of the existing lithium-ion battery electrolyte cannot be guaranteed. Summary of the invention

[0008] The object of the present invention is to provide a method for preparing an efficient lithium-ion battery electrolyte based on a novel polymer, so as to solve the problems raised in the above-mentioned background technology.

[0009] To achieve the above object, the present invention provides the following technical solution: a method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer, comprising a lithium salt, a solvent, an organic plasticizer, a nanofiller, a polymer matrix and a functional additive. The method for preparing the high-efficiency lithium-ion battery electrolyte is as follows:

[0010] S1. Dissolving a selected lithium salt, an organic plasticizer and a polymer matrix in a solvent in a certain proportion to obtain a mixed solution, wherein the lithium salt is LiPF6, the organic plasticizer is propylene carbonate, the polymer matrix is ​​polyimide, and the solvent is an ionic liquid and a supercritical carbon dioxide solvent;

[0011] S2, using a stirring device, at a suitable stirring speed and time, to uniformly disperse the mixed solution in S1 at a molecular level;

[0012] S3, adding functional additives to the mixed solution and mixing them evenly, and obtaining electrolytes of different forms according to the added functional additives, including electrolyte solutions and colloidal electrolytes, wherein the functional additives include lithium salt stabilizers, interface modifiers, SiO 2 aerogel materials, N,N'-dimethyltrifluoroacetamide, and custom-synthesized ligands;

[0013] S4, after the polymerization reaction is completed, a polymer electrolyte is obtained, wherein the polymer electrolyte includes a composite polymer electrolyte and a gel polymer electrolyte;

[0014] S5, removing residual impurities in the polymer electrolyte by vacuum drying;

[0015] S6. Conduct comprehensive performance tests on the prepared polymer electrolyte.

[0016] Preferably, the custom synthesized ligand comprises tetraoxacyclododecane or hexaoxatetracosane.

[0017] Preferably, both tetraoxacyclododecane and hexaoxatetracosane are coordinated with Li+ to form a stable complex by introducing methyl, ethyl, amino, hydroxyl or connecting imidazole.

[0018] Preferably, in S2, during the process of uniformly dispersing the mixed solution, the stirring state is checked regularly to ensure that there is no precipitation and no stratification.

[0019] Preferably, in S3, nanofillers are added to the prepared colloidal electrolyte, and then a crosslinking agent is added to form a three-dimensional network structure between polymer chains through a polymerization reaction, wherein the crosslinking agent is diisopropylbenzene peroxide, and the nanofillers added to the colloidal electrolyte are silicon dioxide or titanium dioxide.

[0020] Preferably, before adding the nanofiller, the nanofiller is treated with vinyltriethoxysilane to impart active functional groups on the surface of the nanofiller that can react with polymer chains or crosslinking agents, wherein the active functional groups include hydroxyl, carboxyl, amino or double bonds.

[0021] Preferably, the added amount of the cross-linking agent accounts for 0.37% of the polymer mass.

[0022] Preferably, the lithium salt stabilizer is vinylene sulfate, and the interface modifier includes vinylene carbonate or fluoroethylene carbonate.

[0023] Preferably, the functional additives further include vinylene carbonate, conductive carbon black, trimethyl phosphate, biphenyl and magnesium oxide.

[0024] Preferably, the ionic liquid is 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and N-methyl-N-propylpiperidinium bis(trifluoromethylsulfonyl)imide.

[0025] Compared with the prior art, the present invention has the following beneficial effects:

[0026] 1. The polymer electrolyte of the present invention can achieve high ion conductivity through reasonable molecular design and polymerization reaction, ensure the rapid transmission of lithium ions in the battery, reduce the migration resistance of ions during the transmission process, effectively improve the ionic conductivity of the electrolyte, and ensure that lithium ions can still migrate quickly and smoothly between the positive and negative electrodes in a low temperature environment, thereby avoiding the problem of discharge capacity attenuation caused by decreased conductivity, so that the battery can still maintain a high working efficiency under extremely cold conditions, and by adding a variety of different functional additives, the diffusion resistance of lithium ions in the electrolyte is reduced, and its non-selective reaction on the electrode surface is reduced, thereby improving the cycle efficiency and overall performance of the battery.

[0027] 2. The present invention introduces reversible cross-linking points so that when the gel polymer electrolyte is mechanically damaged, its integrity can be restored through the dynamic reorganization and repair mechanism of the cross-linking points, thereby extending the service life of the electrolyte, reducing the scrap rate caused by electrolyte damage, and improving production efficiency.

[0028] 3. The present invention combines the advantages of ionic liquids and supercritical carbon dioxide solvents to effectively prevent the decomposition of lithium salts and retain the functional components of the electrolyte to the maximum extent. It can not only effectively prevent the aggregation and precipitation of lithium ions and improve the utilization rate of lithium ions, but also enable lithium ions to more smoothly cross the interface between the electrolyte and the electrode during the transmission process. Under low temperature conditions, it can significantly reduce the energy loss during lithium ion transmission, so that the battery can maintain a high energy density while also showing excellent low-temperature discharge performance, which helps to improve the conductivity and electrochemical stability of the electrolyte, and provides a strong guarantee for the long-term stable operation of lithium batteries in low temperature environments. It can also achieve green production, improve production efficiency and reduce costs.

[0029] 4. The present invention introduces a polymer matrix, utilizes its unique molecular chain structure and the interaction between the electrolyte components, and through the compounding of different polymer matrices, combines the advantages of each single polymer, effectively improves the low-temperature fluidity of the electrolyte, reduces the viscosity, and promotes the migration of lithium ions between the electrode and the electrolyte. To a certain extent, it can significantly improve the low-temperature discharge performance and cycle stability of lithium-ion batteries. DETAILED DESCRIPTION

[0030] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention. Embodiment 1

[0031] A method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer, comprising a lithium salt, a solvent, an organic plasticizer, a nanofiller, a polymer matrix and a functional additive. The method for preparing the high-efficiency lithium-ion battery electrolyte is as follows:

[0032] S1. Dissolving a selected lithium salt, an organic plasticizer and a polymer matrix in a solvent in a certain proportion to obtain a mixed solution, wherein the lithium salt is LiPF6, the organic plasticizer is propylene carbonate, the polymer matrix is ​​polyimide, and the solvent is an ionic liquid and a supercritical carbon dioxide solvent;

[0033] The ionic liquids are 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and N-methyl-N-propylpiperidinium bis(trifluoromethylsulfonyl)imide;

[0034] S2, using a stirring device, at a suitable stirring speed and time, to uniformly disperse the mixed solution in S1 at a molecular level;

[0035] In S2, during the process of uniformly dispersing the mixed solution, the stirring state is regularly checked to ensure that there is no precipitation and no stratification.

[0036] S3, adding functional additives to the mixed solution and mixing them evenly, and obtaining electrolytes of different forms according to the added functional additives, including electrolyte solutions and colloidal electrolytes, wherein the functional additives include lithium salt stabilizers, interface modifiers, SiO 2 aerogel materials, N,N'-dimethyltrifluoroacetamide, and custom-synthesized ligands;

[0037] In S3, a nanofiller is added to the prepared colloidal electrolyte, and then a cross-linking agent is added to form a three-dimensional network structure between polymer chains through a polymerization reaction, wherein the cross-linking agent is diisopropylbenzene peroxide, and the nanofiller added to the colloidal electrolyte is silicon dioxide or titanium dioxide;

[0038] Before adding nanofillers, the nanofillers were treated with vinyl triethoxysilane to give the nanofillers active functional groups on their surfaces that can react with polymer chains or crosslinkers. The active functional groups include hydroxyl, carboxyl, amino or double bonds. The amount of crosslinker added was 0.37% of the polymer mass.

[0039] Custom-synthesized ligands include tetraoxacyclododecane or hexaoxacoxadecane, both of which are coordinated with Li+ to form stable complexes by introducing methyl, ethyl, amino, hydroxyl or connecting imidazole;

[0040] The lithium salt stabilizer is vinylene sulfate, the interface modifier includes vinylene carbonate or fluoroethylene carbonate, and the functional additives also include vinylene carbonate, conductive carbon black, trimethyl phosphate, biphenyl and magnesium oxide;

[0041] S4, after the polymerization reaction is completed, a polymer electrolyte is obtained, wherein the polymer electrolyte includes a composite polymer electrolyte and a gel polymer electrolyte;

[0042] S5, removing residual impurities in the polymer electrolyte by vacuum drying;

[0043] S6. Conduct comprehensive performance tests on the prepared polymer electrolyte.

[0044] Furthermore, by adding different functional additives, lithium-ion battery electrolytes of different forms can be prepared, so that they can improve ion conductivity while ensuring good mechanical properties, and can also reduce the probability of thermal runaway under extreme conditions, thereby improving the overall performance of lithium-ion batteries;

[0045] The addition of N,N'-dimethyltrifluoroacetamide can reduce the viscosity of the composite polymer electrolyte, and can have good film-forming ability on the graphite surface and good oxidation stability to the positive electrode. The addition of the interface modifier can chemically react with the surface of the electrode material to form a dense and stable solid electrolyte interface film. This interface film can not only effectively isolate the direct contact between the electrode and the electrolyte and reduce the occurrence of side reactions, but also protect the electrode material from electrolyte corrosion, thereby significantly improving the interface stability and cycle life of the battery. In a low temperature environment, the interface film can effectively prevent short circuit problems caused by electrolyte solidification or lithium dendrite growth, ensuring the safe operation of the battery.

[0046] The carefully designed polymer chain segments can not only effectively promote the dissociation of lithium salts, making the lithium salt molecules more evenly distributed in the electrolyte, but also significantly reduce the migration resistance of ions during the transmission process, which can effectively improve the ionic conductivity of the electrolyte, especially in low temperature environments, ensuring that lithium ions can quickly and smoothly migrate between the positive and negative electrodes, thereby avoiding the problem of discharge capacity attenuation caused by decreased conductivity. The flexibility of the polymer chain segments also enhances the antifreeze performance of the electrolyte, allowing the battery to maintain a high working efficiency under extremely cold conditions;

[0047] When gel polymer electrolytes are subjected to external damage such as mechanical stress, thermal stress or chemical corrosion, cracks or holes will form in the damaged area. In the damaged area, the reversible cross-linking points will break, resulting in local destruction of the polymer network. At this time, the Diels-Alder reaction or dynamic covalent bonds can trigger the self-repair process of the gel polymer electrolyte through external stimuli such as heating, light, pressure or introduction of catalysts. These stimuli can promote the reconnection or reorganization of the broken reversible cross-linking points.

[0048] Hexaoxa-tetracosane itself has a large ring structure, its internal space is relatively large, and the radius of the Li+ ion is small. In order to make it effectively combine with Li+, we can first consider appropriately modifying the ring structure of hexaoxa-tetracosane to adjust the size and shape of its internal space, that is, designing and synthesizing organic molecules with specific sizes and functional groups to meet specific complexing requirements and make them more suitable for Li+. For example, by introducing appropriate substituents on the ring, such as small alkyl groups such as methyl and ethyl, the flexibility and steric hindrance of the ring can be changed to make the internal space more compact to better wrap Li+.

[0049] The ring structure of tetraoxocyclododecane itself is relatively small, and the size and shape of the ring can be fine-tuned by introducing appropriate substituents on the ring. For example, introducing small alkyl groups such as methyl or ethyl on the carbon atoms of the ring can change the flexibility of the ring and the size of the internal space to a certain extent, so that the ring cavity fits the ion radius of Li+ more closely. At the same time, the introduction of such substituents will also affect the steric hindrance of the ring, which helps to control the direction and method of Li+ entering the ring, thereby optimizing the binding effect.

[0050] Nanofillers can adsorb polymer chains. When polymer chains are cross-linked, nanofillers act like nodes, and diisopropyl peroxide decomposes under certain conditions to produce free radicals. These free radicals can trigger addition reactions of double bonds on polymer chains, connecting different polymer chains together, thereby constructing a three-dimensional network structure with high stability, so that the three-dimensional network structure can maintain its morphology and performance. When polymerization and cross-linking are carried out simultaneously, the polymer chains produced by the polymerization reaction provide reactants for the cross-linking reaction. As the polymerization reaction proceeds, the concentration of polymer chains increases, and the number of active functional groups also increases, making the three-dimensional network structure more perfect. At the same time, the cross-linking reaction can limit the excessive growth and movement of polymer chains, which helps to control the degree of polymerization and the molecular weight distribution of the polymer. For example, in a system where free radical polymerization and cross-linking reactions are carried out simultaneously, the formation of cross-linking points can reduce the free radical activity of the polymer chain, avoid excessive chain growth and branching, and thus make the polymerization reaction more controllable. Embodiment 2

[0051] The selected raw materials include LiPF6, organic plasticizers, polymer matrix, vinylene sulfate, interface modifiers, N,N'-dimethyltrifluoroacetamide, custom-synthesized ligands, ionic liquids and supercritical carbon dioxide solvents. Vinylene carbonate, conductive carbon black, trimethyl phosphate, biphenyl and magnesium oxide can also be added according to preparation requirements.

[0052] Furthermore, the interface modifier is selected as vinylene carbonate or fluoroethylene carbonate, and the electrolytes prepared from the two have no difference in performance;

[0053] Vinyl sulfate improves the cycle stability of lithium-ion batteries by inhibiting the decrease in initial battery capacity and reducing battery expansion after high-temperature storage, thereby extending the battery's service life and charge and discharge efficiency.

[0054] N,N'-dimethyltrifluoroacetamide has good film-forming ability on the graphite surface and good oxidation stability on the positive electrode. The assembled battery has excellent cycle performance at low temperature.

[0055] Vinylene carbonate is a film-forming additive that reduces and effectively passivates the electrode surface under high potential conditions to form a stable SEI film

[0056] Conductive carbon black is a conductive additive, mainly used to improve the dissolution and ionization of conductive lithium salts and prevent the destruction of electrodes by solvent co-insertion;

[0057] Trimethyl phosphate is a flame retardant additive, which improves the stability of the electrode liquid by adding some high boiling point, high flash point and non-flammable solvents;

[0058] Biphenyl is an overcharge protection additive. By adding a suitable redox pair to the electrolyte, this redox pair does not participate in any chemical or electrochemical reaction during normal charging. When the battery is fully charged or slightly above this value, the additive begins to oxidize at the positive electrode and then diffuses to the negative electrode for reduction reaction.

[0059] Magnesium oxide is an additive for controlling the water and HF content in the electrolyte. It reacts with trace amounts of HF in the electrolyte to reduce the HF content, prevent it from damaging the electrode and catalyzing the decomposition of LiPF6, and improve the stability of the electrolyte, thereby improving battery performance. Embodiment 3

[0060] The selected raw materials include LiPF6, organic plasticizer, polymer matrix, SiO 2 Aerogel materials and nanofillers.

[0061] Furthermore, by introducing a variety of nanofillers with different functions into the colloidal electrolyte, multifunctional composite modification can be achieved, or by using layer-by-layer self-assembly technology to construct functional nanolayers on the surface or inside the electrolyte, thereby giving the electrolyte new properties, and by introducing reversible cross-linking points, a gel polymer electrolyte with self-healing function can be prepared.

[0062] Comparative Example 1:

[0063] Compared with Example 2, both are composite polymer electrolytes, but N,N'-dimethyltrifluoroacetamide is not added.

[0064] Comparative Example 2:

[0065] Compared with Example 2, both are composite polymer electrolytes, and the solvent used is a solvent system of EC:DMC:EMC:FEC:F-EPE in a mass ratio of 1:1.5:1:1:0.5.

[0066] Comparative Example 3:

[0067] Compared with Example 3, both are gel polymer electrolytes, but no nano filler is introduced.

[0068] Experimental example,

[0069] Regarding the test of ionic conductivity: high-precision electrochemical impedance spectroscopy is used, which can accurately capture the dynamic process of ion transport inside the electrolyte.

[0070] Thermal stability test: simulates the application scenarios of lithium-ion batteries in extreme environments at -40°C to 80°C.

[0071] Ionic conductivity of Example 2, Example 3, and Comparative Examples 1, 2, and 3 under different temperature scenarios:

[0072]

[0073] Experimental results show that the ionic conductivity of the new polymer electrolyte has achieved a significant leap, which not only reflects the efficient construction and optimization of its internal ion channels, but also indicates that faster charging and discharging rates and higher energy conversion efficiency can be achieved in battery applications. Specifically, the improvement in ionic conductivity means that under the same conditions, the new electrolyte can transfer charge from the positive electrode to the negative electrode, or back from the negative electrode to the positive electrode, faster, reducing the energy loss caused by the internal resistance of the battery, thereby extending the battery life.

[0074] Electrochemical stability: The electrolyte prepared in the present application was assembled into lithium-ion batteries, recorded as composite battery packs and gel battery packs, and the electrolyte prepared in the comparative example was assembled into lithium-ion batteries, recorded as ordinary battery packs, and cyclic charge and discharge tests were performed at the same time;

[0075] The battery discharge capacity of Examples 2, 3 and Comparative Example:

[0076]

[0077] Through long-term cyclic charge and discharge tests, the new electrolyte has demonstrated remarkable thermal and electrochemical stability. Its molecular structure can still maintain a high degree of integrity under extreme temperatures, with no obvious signs of capacity decay or structural damage.

[0078] Mechanical properties: Samples were taken from the composite polymer electrolyte and gel polymer electrolyte prepared in Example 2 and Example 3 of the present application, and cut into samples of appropriate sizes after treatment, recorded as Sample 1 and Sample 2. Samples were taken from the composite polymer electrolyte and gel polymer electrolyte prepared in Comparative Example 1, Comparative Example 2 and Comparative Example 3 of the present application, and vacuum dried to obtain dry electrolyte films, which were cut into the same size as Sample 1 and Sample 2. The average value was taken and recorded as the reference product. Then, a tensile testing machine was used to test the tensile strength and elongation at break of Sample 1, Sample 2 and the reference product, respectively.

[0079] Safety performance test: The new electrolyte was comprehensively tested under a variety of extreme conditions including needle puncture and overcharging. During the experiment, the new electrolyte demonstrated excellent safety performance, and no safety accidents such as combustion or explosion occurred. This result was attributed to its high chemical stability and thermal stability. While ensuring efficient ion transmission, it optimized the molecular structure and interface compatibility, effectively inhibiting the occurrence of side reactions and the rapid accumulation of heat, thereby improving the safety of the battery system from the source.

[0080] It will be apparent to those skilled in the art that the present invention is not limited to the details of the exemplary embodiments described above and that the present invention can be implemented in other specific forms without departing from the spirit or essential features of the present invention. Therefore, the embodiments should be considered exemplary and non-restrictive in all respects, and the scope of the present invention is defined by the appended claims rather than the above description, and it is intended that all changes falling within the meaning and scope of the equivalent elements of the claims be included in the present invention.

Claims

1. A method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer, characterized in that: The preparation method of the high-efficiency lithium-ion battery electrolyte comprising lithium salt, solvent, organic plasticizer, nanofiller, polymer matrix and functional additive is as follows: S1, dissolving the selected lithium salt, organic plasticizer and polymer matrix in a solvent in a certain proportion to obtain a mixed solution, wherein the lithium salt is LiPF6, the organic plasticizer is propylene carbonate, the polymer matrix is ​​polyimide, and the solvent is an ionic liquid and a supercritical carbon dioxide solvent; S2, using a stirring device, at a suitable stirring speed and time, to uniformly disperse the mixed solution in S1 at a molecular level; S3, adding functional additives to the mixed solution and mixing them evenly, and obtaining electrolytes of different forms according to the added functional additives, including electrolyte solutions and colloidal electrolytes, wherein the functional additives include lithium salt stabilizers, interface modifiers, SiO2 aerogel materials, N,N'-dimethyltrifluoroacetamide and custom-synthesized ligands, and the custom-synthesized ligands include tetraoxacyclododecane or hexaoxa-tetracosane; S4, after the polymerization reaction is completed, a polymer electrolyte is obtained, wherein the polymer electrolyte includes a composite polymer electrolyte and a gel polymer electrolyte; S5, removing residual impurities in the polymer electrolyte by vacuum drying; S6. Conduct comprehensive performance tests on the prepared polymer electrolyte.

2. The method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer according to claim 1, characterized in that: Both tetraoxacyclododecane and hexaoxacoxadecane form stable complexes by coordinating with Li+ by introducing methyl, ethyl, amino, hydroxyl or connecting imidazole.

3. The method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer according to claim 1, characterized in that: In S2, during the process of uniformly dispersing the mixed solution, the stirring state is regularly checked to ensure that there is no precipitation and no stratification.

4. The method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer according to claim 1, characterized in that: In S3, nanofillers are added to the prepared colloidal electrolyte, and then a crosslinking agent is added to form a three-dimensional network structure between polymer chains through a polymerization reaction, wherein the crosslinking agent is diisopropylbenzene peroxide, and the nanofillers added to the colloidal electrolyte are silicon dioxide or titanium dioxide.

5. The method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer according to claim 4, characterized in that: Before adding the nanofiller, the nanofiller is treated with vinyl triethoxysilane so that the surface of the nanofiller has active functional groups that can react with polymer chains or crosslinking agents. The active functional groups include hydroxyl, carboxyl, amino or double bonds.

6. The method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer according to claim 4, characterized in that: The added amount of the crosslinking agent accounts for 0.37% of the polymer mass.

7. The method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer according to claim 1, characterized in that: The lithium salt stabilizer is vinylene sulfate, and the interface modifier includes vinylene carbonate or fluoroethylene carbonate.

8. The method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer according to claim 1, characterized in that: Functional additives also include vinylene carbonate, conductive carbon black, trimethyl phosphate, biphenyl and magnesium oxide.

9. The method for preparing a high-efficiency lithium-ion battery electrolyte based on a novel polymer according to claim 1, characterized in that: The ionic liquids are 1-ethyl-3-methylimidazolium bis(trifluoromethylsulfonyl)imide and N-methyl-N-propylpiperidinium bis(trifluoromethylsulfonyl)imide.

Citation Information

Patent Citations

  • Preparation method of high voltage electrolyte used for lithium ion battery

    CN104752770A

  • Battery cell of polymer lithium ion battery and polymer lithium ion battery

    CN108134128A

  • Method for preparing lithium ion battery employing organic-inorganic composite gel polymer electrolyte

    CN109546205A

  • Polymer lithium ion battery and preparation method thereof

    CN111916835A

  • Power storage device, and sheet-form solid electrolyte for power storage device

    WO2021130920A1